Preliminary study of improving immune tolerance in vivo of bioprosthetic heart valves through a novel antigenic removal method - Song, Mingzhe; Yi, Liang; Tang, Zhenjie; Xie, Xinlong; Liu, Yuhong; Qi, XiaoKe; Jiang, Zhenlin; Chen, ZeGuo; Chen, Chunyang; Wu, QiYing; Wu, ZhongShi (Frontiers in Bioengineering and Biotechnology, 2023)
The durability of bioprosthetic heart valves is often compromised by the inherent antigenicity of biomaterials. Decellularization has been a promising approach to reducing the immunogenicity of biological valves. However, current methods are insufficient in eliminating all immunogenicity from the biomaterials, necessitating the exploration of novel techniques. In this study, we investigated the use of a novel detergent, fatty alcohol polyoxyethylene ether sodium sulfate (AES), to remove antigens from bovine pericardium. Our results demonstrated that AES treatment achieved a higher pericardial antigen removal rate compared to traditional detergent treatments, while preserving the mechanical properties and biocompatibility of the biomaterials. Moreover, in our in vivo rat model, we observed excellent immune tolerance. Overall, our findings suggest that AES treatment is a promising method for preparing biological valves with ideal clinical application prospects.